HAMBATAN PENYALURAN DANA BANTUAN OPERASIONAL SEKOLAH (STUDI KASUS DI PROPINSI SUMATERA UTARA) - Yuris Danilwan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
In general, the study aims to see how far the effective use of policy implementation disbursements School Operational Assistance (BOS), which has been implemented so far in order to free tuition. The research involves several elements like: PIU Office Level II, Personnel at Bank dealer, School Committee, Principal and Students who are in districts north Sumatra province. This research also involves a number of factors thought to be determinants of implementation effectiveness of the School Operational Assistance (BOS) in the field. Statistical methods used are modeling Structural Equation Modeling (SEM). This research was carried out in Medan. Location of the study Elementary and Junior High School. Respondents totaled 554 respondents. The results showed that: a). All factors considered valid or have a significant influence on the formation of each latent variable, namely: latent variable input, process, output and outcome. b). The amount of the direct influence of input variables to process variables of 0.83. While the contribution of 68.89%. c). There is a direct influence of input variables on output variables. The amount of the direct influence of input variables on output variables of 0.21. While the direct contribution given by the input variables on output variables of 4.41%. d). There are no direct influence on the input variables Outcome variables. The amount of indirect effect through the Input variable Output variable to the outcome variable that is equal to 0.162. While the contributions made by variable input through output variables Outcome variables at 2.61%. e). There is an indirect effect through the variable Input Variable Process and proceed through a variable output to outcome variables. The amount of indirect effect through the variable process input variables and proceed through a variable output to outcome variables of 0.50. Contributions made 25.49%. f). The influence of each factor formed on the latent variables of input, process and output of the factors increasing the value of education and National Final Test (UAN).